Pectoralis Major (Breast) Muscle Extracellular Matrix Fibrillar Collagen Modifications Associated With the Wooden Breast Fibrotic Myopathy in Broilers - Velleman, Sandra G. (Frontiers in Physiology, 2020)
The poultry industry has placed significant emphasis on the selection of meat-type broilers for increased body weight, increased meat yield especially the pectoralis major (breast) muscle, decreased time to processing, and improved feed conversion. Although significant improvements have occurred in fast-growing meat-type broilers, myopathies affecting meat quality especially in the pectoralis major muscle have occurred. Many of the broiler breast muscle myopathies are caused by inflammation leading to the necrosis of existing muscle fibers and resulting in replacement of the muscle fibers with extracellular matrix proteins especially fibrillar collagens, fibrosis. This review explores how the fibrotic deposition and organization of extracellular matrix proteins especially the fibrillar collagens, Types I and III, affects the phenotype of the Wooden Breast myopathy, functional properties of the pectoralis major muscle, and meat quality.